ICT Innovations 2018 : engineering and life sciences : 10th International Conference, ICT Innovations 2018, Ohrid, Macedonia, September 17-19, 2018, Proceedings /: engineering and life sciences : 10th International Conference, ICT Innovations 2018, Ohrid, Macedonia, September 17-19, 2018, Proceedings. (2018) - Unknown
No abstract available